Characteristics of loess landslides triggered by the 1927 Mw8.0 earthquake that occurred in Gulang County, Gansu Province, China - Zhong, Xiumei; Xu, Xiaowei; Chen, Wenkai; Liang, Yuxin; Sun, Qinyao (Frontiers in Environmental Science, 2022)
The 1927 Gulang Mw8.0 earthquake was one of the largest earthquakes in Gansu, China, which triggered lots of loess landslides. However, the loess of the study area is atypical and different from that of the Loess Plateau. Meanwhile, there are few systematic research studies on the characteristics of these seismic landslides. Combined with previous studies and field investigations, the landslide distribution has been revealed through the visual interpretation of remote sensing images of the study area. The relationships between landslides and various influencing factors have been explored through spatial analysis of geographic information science (GIS). Furthermore, comparisons have been made between the Gulang earthquake landslides and other seismic landslides in the Loess Plateau from macroscopic and microcosmic perspectives. A total of 807 earthquake landslides have been interpreted, with a total landslide area of 256.14 km2. The region with the seismic intensity of Ⅹ is the dominant area of landslide distribution. Also, most landslides are distributed at slope angles of (10° and 40°). The relative elevation difference of (100 m and 300 m) is the high-incidence range of landslides. Compared with seismic landslides in the Loess Plateau, the slope angle and the relative elevation difference of most landslides in the study area are larger. The strength of the loess structure in the study area is stronger than that in the Loess Plateau from the view of physical properties and microstructure.